RECEPTIVE SKILLS AMONG B.Ed. TRAINEES - N. Archana; K. Somasundaram (International Journal of Research -GRANTHAALAYAH, 2017)
Language and life are inter-related. The scope of language is widened with the widening scope of human activity. Today there is no activity, which does not find its expression in terms of language. Listening and reading are passive or receptive skills and speaking and writing are active or productive skills. The paper is an attempt to find to identify the receptive skills in English among B.Ed trainees. The investigator adopted the survey method to study receptive skills of B.Ed trainees. The study is based on primary data which is collected from 300 BEd trainees in and around Coimbatore district using simple random sampling technique. The findings reveal that totally 25% of the selected B.Ed. trainees belong to low level of receptive skill, 46.6% of the selected BEd trainees belong to moderate level of receptive skill, 26.6% of the selected BEd trainees belong to high level of receptive skill. Also it is found that there is no significant difference in receptive among the selected B.Ed trainees based on gender and locality.